Perlindungan Terhadap Pengungsi dan Pencari Suaka di Indonesia Pada Masa Pandemi Covid-19 - Edelweisia Cristiana (IAHN Tampung Penyang Palangka Raya, 2021)
The purpose of writing about the protection of foreign refugees and asylum seekers in Indonesia during the Covid-19 pandemic are to examine the factual conditions in Indonesia as a transit country and to compile various regulations that underlie human rights. This research was conducted through a statutory approach, a literature study, and a case approach. The research used a normative legal research method and the type of analysis applied was descriptive interpretive. The results of this paper include immigration regulations as the basis for accepting foreign refugees and asylum seekers in Indonesia; obtaining data regarding the conditions of foreign refugees and asylum seekers in Indonesia who have not received optimal protection during the Covid-19 pandemic; and a number of regulations protecting the rights of foreign refugees and asylum seekers in Indonesia.